Foresight for Danube Region’s Future-Oriented Competitive Planning: Book of Abstracts (University of Maribor Press, 2025)
The ForeDanube initiative and its related activities collectively advance the role of foresight as a strategic instrument for competitiveness, innovation, and resilient policymaking in the Danube Region. Across nine contributions, the presentations address both theoretical and applied dimensions of foresight: from integrating artificial intelligence and managing uncertainty, to strengthening education through a dedicated Master’s program, embedding foresight into the EU Strategy for the Danube Region, and supporting crisis preparedness. Empirical insights from regional surveys highlight the gap between awareness and practice, while practical frameworks, such as the Danube Transfer Centre network and structured work plans, demonstrate how foresight can be institutionalized across multi-level governance. EU co-financing opportunities through Horizon Europe are identified as crucial enablers for capacity building. The overarching vision culminates in the ForeDanube project’s proposal for a permanent Foresight Competence Centre, serving as a hub for anticipatory governance and as a scalable model for Europe and beyond.